Ergonomic fertilizer bag / Muhammad Wafiq Roslan, Nur Anati Mohd Jamaluddin and Norezzah Nazwa Mohd Sukri - Roslan, Muhammad Wafiq; Jamaluddin, Nur Anati Mohd; Mohd Sukri, Norezzah Nazwa (Faculty of Plantation and Agrotechnology, 2023)
An ergonomic fertilizer bag is one that minimizes back pain and prevents musculoskeletal disorders among workers during the fertilization process. This innovation is designed in the style of an ergonomic backpack and includes new features such as a herbal organic sponge that provides workers with extra comfort and acts as a heat absorber. We developed this ergonomic fertilizer bag and conducted research on it because it was not yet available on the market. According to a survey and experience on the plantation, the majority of workers prefer this ergonomic fertilizer bag to maintain their bodies health. For future action, this innovation must be addressed with other authorities.